Modeling manufacturer's capabilities for the Internet of Things - Hasselblatt, Mathias; Huikkola, Tuomas; Kohtamäki, Marko; Nickell, David (Emerald, 2018)
Purpose - The study identifies a s abilities to develop, build, sell and deliver IoT services. Design/methodology/approach - A qualitative comparative case method that uses multiple sources of data, including executive interviews and secondary data, to understand a manufacturer's IoT capabilities. Findings - Five Internet of Things (IoT) capabilities were identified: 1) digital business model development, 2) scalable solution platform building, 3) value selling, 4) value delivery, and 5) business intelligence (BI) and measurement. Research limitations/implications - The main limitations are related to the qualitative research method applied. The results are applicable mainly to relatively large and global manufacturers. Practical implications - Managers responsible for solution business development can apply the developed model to acquire and manage IoT specific resources, processes, and capabilities. Originality/value - Existing studies have not addressed the IoT-specific resources, processes, and capabilities that manufacturers' possess. This is one of the first studies to conceptualize how these capabilities are employed.
Keywords: business intelligence; digitalization; industrial internet; Internet of Things; resource-based view; servitization